Investigation of the Geomagnetically Induced Current Index Levels in the Mediterranean Region During the Strongest Magnetic Storms of Solar Cycle 24 - A. Z. Boutsi; G. Balasis; S. Dimitrakoudis; I. A. Daglis; K. Tsinganos; C. Papadimitriou; O. Giannakis (Space Weather, 2023)
Abstract Geomagnetically induced currents (GICs) constitute an integral part of space weather research and are a subject of ever‐growing attention for countries located in the low and middle latitudes. A series of recent studies highlights the importance of considering GIC risks for the Mediterranean region. Here, we exploit data from the HellENIc GeoMagnetic Array, which is deployed in Greece, complemented by magnetic observatories in the Mediterranean region (Italy, France, Spain, Algeria, and Turkey), to calculate values of the GIC index, that is, a proxy of the geoelectric field calculated entirely from geomagnetic field variations. We perform our analysis for the most intense magnetic storms (Dst < −150 nT) of solar cycle 24. Our results show that GIC index increases are well correlated with storm sudden commencements. However, the GIC indices do not exceed “low” activity levels despite the increases in their values, at all magnetic stations/observatories under study during the selected storm events.